The Arctic Polar-night Jet Oscillation - Hitchcock, Adam Peter
The eastward winds that form each winter in the Arctic stratosphere are intermittently disrupted by planetary-scale waves propagating up from the surface in events known as stratospheric sudden warmings. It is shown here that following roughly half of these sudden warmings, the winds take as long as three months to recover, during which time the polar stratosphere evolves in a robust and predictable fashion. These extended recoveries, termed here Polar-night Jet Oscillation (PJO) events, are relevant to understanding the response of the extratropical troposphere to forcings such as solar variability and climate change. They also represent a possible source of improvement in our ability to predict weather regimes at seasonal timescales. Four projects are reported on here. In the first, the approximation of stratospheric radiative cooling by a linear relaxation is tested and found to hold well enough to diagnose effective damping rates. In the polar night, the rates found are weaker than those typically assumed by simplified modelling studies of the extratropical stratosphere and troposphere. In the second, PJO events are identified and characterized in observations, reanalyses, and a comprehensive chemistry-climate model. Their observed behaviour is reproduced well in the model. Their duration correlates with the depth in the stratosphere to which the disruption descends, and is associated with the strong suppression of further planetary wave propagation into the vortex. In the third, the response of the zonal mean winds and temperatures to the eddy-driven torques that occur during PJO events is studied. The collapse of planetary waves following the initial warming permits radiative processes to dominate. The weak radiative damping rates diagnosed in the first project are required to capture the redistribution of angular momentum responsible for the circulation anomalies. In the final project, these damping rates are imposed in a simplified model of the coupled stratosphere and troposphere. The weaker damping is found to change the warmings generated by the model to be more PJO-like in character. Planetary waves in this case collapse following the warmings, confirming the dual role of the suppression of wave driving and extended radiative timescales in determining the behaviour of PJO events. PhD